Plithogenic multi‐criteria decision making approach on airspace planning scheme evaluation based on ATC‐flight real‐time simulation. Issue 11 (2nd July 2022) - Liang, Binbin; Han, Songchen; Li, Wei; Han, Yunxiang; Liu, Fan; Zhang, Ying; Lin, Chen
Abstract: Airspace planning scheme evaluation based on ATC‐Flight real‐time simulation which incorporates air traffic control simulator and flight simulator has become increasingly important. It has irreplaceable advantages of truly simulating and in‐depth evaluating airspace operation, especially for analyzing human factors. As a multi‐criteria decision making (MCDM) problem, it poses challenges which this study aims to overcome from three aspects. Firstly, the complexity of airspace and the characteristics of ATC‐Flight real‐time simulation are analyzed to build a multi‐criteria evaluation system. The criteria include air traffic flow, airspace operational performance, flight procedure quality, cost, controller workload and pilot workload. Secondly, a novel weighting method based on plithogenic set is presented to derive robust subjective criteria weights from a group of human decision makers. The subjective weights are then combined with objective weights using game theory to determine cumulative criteria weights. Thirdly, technique for order preference by similarity to ideal solution (TOPSIS) and grey correlation analysis are integrated to perform comprehensive evaluation and ranking. The first series of ATC‐Flight real‐time simulations in China are conducted to illustrate a case study. The results demonstrated that the proposed MCDM approach could improve the accuracy and discriminability of evaluation results, and outperformed other existing well‐known MCDM algorithms.